Pemberdayaan Kepemimpinan Kepala Sekolah Dasar di SD Negeri 1 Nambuhan Kecamatan Purwodadi Kabupaten Grobogan - Sukardi, Sukar Al; , Prof. Dr. Bambang Sumardjoko; , Dr. Sumardi, M.Si (2016)
ABSTRACT Al Sukardi difficult. Q.100.140.013. Empowering leadership elementary school principal in SD Negeri 1 Purwodadi Subdistrict Nambuhan Grobogan District. Prof.Dr. Bambang Sumardjoko, Sumardi, M.Si thesis. Graduate Muhammadiyah University of Surakarta 2016. The purpose of this study was to describe (1) Characteristics of Primary School head leadership style in SD Negeri 1 Purwodadi Subdistrict Nambuhan. (2) Characteristics of the principal steps in running leadership SD Negeri 1 Purwodadi Subdistrict Nambuhan (3) Characteristics of the achievements of the leadership of principal in SD Negeri 1 Purwodadi Subdistrict Nambuhan This study is a qualitative research, data collection technique using observation, interviews and documentation. Data analysis technique is done by collecting data: data reduction, data presentation, and conclusion. Test the validity of the data using triangulation sources The results of this study were (1) style leadership that be applicable by the principal of SD Negeri 1 Nambuhan is a democratic leadership style .The principal is always oriented to the interests and goals of the organization, be open, accept criticism and constructive suggestions from subordinates, and also capable of providing guidance, attention and become a role model and firm in enforcing the rules all decisions are taken by consensus shared between teachers and committees. (2) measures undertaken principals SD Negeri 1 Nambuhan District of Purwodadi Grobogan in the running style of leadership is always learn from experience, to evaluate in each activity, provide motivation full of friendly against the teacher of teachers, provide an opportunity for teachers to be creative in order the development of the learning process, and make the teacher as a good partner. (3) the achievements of leadership is perceived by teachers SDNegeri 1 Nambuhan with a leadership style that made so far namely teachers SD Negeri 1 Nambuhan motivated and goaded to create increasing potential. This achievement earned SD Negeri 1 Nambuhan during ongoing leadership is such achievement in the field of sports, religious, once represented, district,provincial standby scouting party always represent the district to the provincial level Keywords: style leadership, empowerment, school principal